Sistem Informasi Pengajuan Judul Tugas Akhir Mahasiswa Program Studi Akuntansi (D3) : Information System for Submission of Final Project Title for Accounting Study Program Students (D3) - David Saro (YCMM, 2020)
The Faculty of Economics and Business, Ibnu Sina University, especially the Accounting study program (D3) in managing the final project still uses the conventional method by using paper media which is used as a title submission form and for recording titles that have been ACC still uses a ledger or recording using Microsoft Word or Excel so that sometimes data management becomes less effective and efficient, therefore it is necessary to design a web-based application so that it can make it easier to record the titles of final assignments that have been ACC or approved. The methods used for data collection are literature, literature study, and observation, while in data processing using data collection methods, business modeling, design, manufacture (construction), system testing, and implementation. This title submission information system is designed as an effort to improve student efficiency in data management for Final Project students of the Faculty of Economics and Business, Accounting Study Program. This information system provides a lot of convenience in submitting the title of the final project for students of the Faculty of Economics and Business, Accounting Study Program, Ibnu Sina University.